How a tectonic earthquake may wake up volcanoes: Stress transfer during the 1996 earthquake–eruption sequence at the Karymsky Volcanic Group, Kamchatka - Walter Thomas R. (My University, 2007)
A large tectonic earthquake occurred on Kamchatka peninsular on New Year's Day of 1996 along a SW–NE trending fracture system. Just two days after the earthquake and at a distance of about 10–20 km to the north, a simultaneous eruption of two separate volcanoes followed. These were Karymsky Volcano and Akademia Nauk Volcano, the latter having its first eruption in historical records. In this paper I use numerical models in order to elaborate the static stress transfer between the earthquake and the volcanic system during the sequence that culminated in the January 1996 volcano-tectonic events. The models were designed to consider (i) the geodetically identified pre-eruptive period of doming in order to calculate stress changes at the nearby SW–NE trending fracture zone, and (ii) the January 1996 Mw 7.1 earthquake in order to calculate the dilatation and stress changes at the magma plumbing system. The results suggest that stress changes related to year-long inflation under the volcanic centers increased the Coulomb failure stress at the active faults and thus encouraged the earthquake. The earthquake, in turn, prompted dilatation at the magmatic system together with extensional normal stress at intruding N–S trending dikes. Also, field measurements confirmed the presence of N–S oriented fractures above the dike. Unclamping of the N–S oriented fractures allowed magma to propagate and eventually to trigger the twin-eruption at the volcanoes Karymsky and Akademia Nauk. These findings imply that successful hazard evaluations at volcanoes elsewhere require consideration of the seismo-tectonic framework and large earthquake cycles.
Keywords: 38.19.17 Землетрясения и сейсмотектоника; Академии Наук; Карымский